Maria Zambrano, a woman who builds to social coexistence - Víllora, Carmen (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
Maria Zambrano’s lifetime develops in Europe and America throughout the 20th century. She is characterized by an energetic and decided behavior in favor of human life. With a deep knowledge of the time she had to live in, she was always aware of the problems of the world, in order to express her opinion and indicate action lines for a hopeful future. In the first section, we will go through her biography to recognize the most significant aspects of her social commitment. In the second part, we will present some ideas from her writings in order to interpret his political and civic participation. We will conclude, in the third fragment, with the proposal of the construction of the city to grow as people and to coexist in peace.